Literature and Journalism in Julian Barnes - Letters from London - Davian Vlad (Social Sciences and Education Research Review)
Well known as an accomplished novelist, Julian Barnes had also a prodigious journalistic career which proved that he had the talent to adopt and adapt both ways of writing and reflecting reality. The peak of his media experience was the period of more than five years spent as the correspondent in Great Britain for the American magazine The New Yorker. The journalistic essays addressed to the public across the Atlantic were later gathered between the covers of a book called Letters from London, a collection of texts that reveal the fascinating way in which a literary writer observe and decode reality in order to explain it to a public that is rather unfamiliar with the actuality in a country far away.